2017
DOI: 10.3945/cdn.116.000232
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Test-Meal Protocols Lead to Blunted Postprandial Lipemia but Similar Inflammatory Responses Compared with a Standard High-Fat Meal

Abstract: Background: A substantial increase in triglycerides (TGs) after a meal is associated with an increased risk of cardiovascular disease. Most studies investigating the effects of a meal on TGs have not used meals that reflect typical consumption. Objective: The objective of this study was to compare the TG and inflammatory responses of true-to-life meals, containing moderate fat and energy contents, with a high-fat, high-energy, low-carbohydrate meal (HFM) typically used to test TG responses. Methods: Nine healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Taguchi and colleagues ( 50 ) determined that a similar quantity of fat (20 g) increased postprandial triglycerides by approximately 1⋅20 mmol/l (approximately 106 mg/dl) in subjects with normal fasting triglycerides <1⋅70 mmol/l (<150 mg/dl). Emerson et al ( 26 ) demonstrated that consuming one moderate fat meal (sausage, egg, cheese, whole-grain crust; 8⋅5 kcal/kg; 30 % fat (13 % saturated fat)) containing similar total fat (22 g fat; 660 kcal), followed by the same meal 3 h later, sustained the initial triglyceride peak and caused approximately 3 % change per hour increase in serum triglycerides over the next 3 h before triglycerides began to decline. If four meals spaced 3 h apart are assumed, and postprandial triglyceride kinetics are similar following the third and fourth meals, we estimate that the average man may experience a triglyceride peak near 3⋅39 mmol/l (300 mg/dl) approximately 7 PM and will not return to baseline until approximately 1 AM ( Fig.…”
Section: Estimated Daily Triglyceride Kinetics In Westernised Countriesmentioning
confidence: 99%
“…Taguchi and colleagues ( 50 ) determined that a similar quantity of fat (20 g) increased postprandial triglycerides by approximately 1⋅20 mmol/l (approximately 106 mg/dl) in subjects with normal fasting triglycerides <1⋅70 mmol/l (<150 mg/dl). Emerson et al ( 26 ) demonstrated that consuming one moderate fat meal (sausage, egg, cheese, whole-grain crust; 8⋅5 kcal/kg; 30 % fat (13 % saturated fat)) containing similar total fat (22 g fat; 660 kcal), followed by the same meal 3 h later, sustained the initial triglyceride peak and caused approximately 3 % change per hour increase in serum triglycerides over the next 3 h before triglycerides began to decline. If four meals spaced 3 h apart are assumed, and postprandial triglyceride kinetics are similar following the third and fourth meals, we estimate that the average man may experience a triglyceride peak near 3⋅39 mmol/l (300 mg/dl) approximately 7 PM and will not return to baseline until approximately 1 AM ( Fig.…”
Section: Estimated Daily Triglyceride Kinetics In Westernised Countriesmentioning
confidence: 99%
“…A strength of the present study was the use of a more realistic test meal with more true-to-life fat levels and energy contents, instead of a very high-fat meal, as the second may not reflect the metabolic state of many individuals in their daily-life [34]. Furthermore, only the male participants were included in the study, which helped in diminishing the potentially confounding effects of female cycles modulating hormone levels on the study parameters.…”
Section: Study Strength and Limitationsmentioning
confidence: 99%
“…While some studies have evaluated the additive effect of realistic, Western-style foods on serum triglycerides over two meals (e.g., [3]), this is the first study to our knowledge to measure triglycerides throughout a 24-h period while simulating a "true-to-life" WD. Adding to the realistic nature of the study, participants were informally screened prior to the study to determine whether their eating habits were similar to our planned intervention, and if participants ate beyond the minimum requirement it was by their own volition.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, this relationship appears to be due to the strong correlation between postprandial triglycerides and triglyceride-rich lipoprotein remnant cholesterol, which is an increasingly appreciated source of residual CVD risk [2]. Postprandial triglycerides may be especially of interest in countries consuming Westernized diets rich in total and saturated fat, as fat from multiple meals has an additive effect on circulating triglycerides throughout the day [3]. However, despite the reality that individuals spend the majority of the day in the postprandial state, studies evaluating the summative effect of high-fat meals on postprandial triglycerides have thus far not examined a full 24-h period or had other limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation